Friction stir welding-based technologies: A comprehensive review from the sustainable manufacturing perspectives - Mohamed I.A. Habba; Mohamed M.Z. Ahmed (Journal of Materials Research and Technology)
Process impact, energy efficiency, and resource conservation are critical in sustainable manufacturing (SM). Friction Stir Welding (FSW) based technologies offer a solid-state joining and processing approach that significantly reduces energy input, material waste, and environmental impact compared with conventional fusion welding methods, making them at the forefront of sustainable manufacturing. By enabling high-integrity joints without the use of consumables, shielding gases, or post-processing treatments, FSWBTs exemplify how advanced manufacturing technologies can directly support the global transition toward cleaner, safer, and more resource-efficient production systems. This review examines FSWBTs in terms of manufacturing sustainability by analyzing their operational principles, industrial implementations, and sustainability contributions. The FSWBTs family, including Friction Stir Welding (FSW), Friction Stir Processing (FSP), and Friction Stir Additive Manufacturing (FSAM), operates in the solid state at sub-melting temperatures, using non-consumable rotational tooling that generates thermal energy and plastic deformation for bonding and material processing. This analysis examines the environmental advantages of FSWBTs, including reduced emissions, elimination of consumables, and enhanced product lifecycle performance. This review assesses the energetic benefits of FSWBTs, focusing on reduced energy requirements, improved process efficiencies, and enhanced productivity. The material conservation aspects and recyclability of FSWBTs were examined, with an emphasis on optimizing material utilization and directly reusing metal waste. This review examines FSWBTs applications in sustainability-focused industries, including electric mobility and renewable energy generation. Methods for sustainability optimization in FSWBTs implementation include tool geometry refinement, process parameter optimization, strategy-assisted FSWBTs, and integration with Industry 4.0. Additionally, developments in the FSWBTs field, which highlight its potential to advance sustainable manufacturing, have been addressed. This analysis highlights the crucial role of FSWBTs as enablers of sustainable manufacturing.